Effects of different vaginal mould use approaches after vaginoplasty with artificial dermis in patients with Mayer–Rokitansky–Küster–Hauser syndrome - Wang, Wenli (J Int Med Res, 2021)
OBJECTIVE: To assess the therapeutic effects of different vaginal mould use approaches after vaginoplasty in patients with Mayer–Rokitansky–Küster–Hauser (MRKH) syndrome. METHODS: Patients with MRKH syndrome who underwent surgery from 2010 to 2015 in our hospital were retrospectively evaluated. Vaginoplasty was performed with artificial dermis, and vaginal moulds were used for 6 months postoperatively. The patients were divided into an intermittent group and continuous group according to the vaginal mould approach. RESULTS: Thirty-five patients were evaluated (intermittent group, 19 patients; continuous group, 16 patients). One month postoperatively, the mean vaginal length and width in the intermittent group were 9.26 ± 0.56 and 3.82 ± 0.25 cm, respectively, and those in the continuous group were 9.44 ± 0.51 and 3.86 ± 0.22 cm, respectively. Six months postoperatively, the mean vaginal length and width in the intermittent group were 8.94 ± 0.71 and 3.76 ± 0.26 cm, respectively, and those in the continuous group were 8.69 ± 0.48 and 3.65 ± 0.30 cm, respectively. The mean Female Sexual Function Index scores in the intermittent and continuous groups were 28.61 ± 0.71 and 28.4 80 ±0.79 respectively, after normal sexual life. CONCLUSION: Both intermittent and continuous use of postoperative vaginal moulds may be effective.